Consumer behaviour towards sustainable business practices: insights from baby boomers and X, Y, Z generational segments (ҚазҰУ хабаршысы. Экономика сериясы, 2020)
This study aims to explore generational differences in consumer attitudes towards sustainable businesspractices of hospitality and tourism firms. The empirical study adopts a quantitative research methodologybased on survey data collection technique using a self-administered questionnaire. ANOVAtests were conducted to determine significant differences between four tested groups. The Tukey HSDtest was used to conduct detailed multiple Post-hoc comparative analysis. Findings suggest that thereis a significant difference between four generations in their attitudes regarding community and naturebasedsustainable business practices of hospitality and tourism companies, while there is no differenceregarding eco-friendly business concepts.This empirical quantitative research advances the generational theory as applied to hotel and restaurantbusiness as well as tourism sectors by exploring behavioral differences and similarities betweenBaby boomers and X, Y, Z generational segments. On the other hand, it contributes empirical evidenceto the holistic knowledge on generational consumer behavior in the under-researched context of Kazakhstan.